Axial performance of seawater sea-sand concrete columns reinforced with basalt fibre-reinforced polymer bars under concentric compressive load. (15th April 2022) - Xiong, Zhe; Lin, Lianghao; Qiao, Sihua; Li, Lijuan; Li, Yinglei; He, Shaohua; Li, Zewei; Liu, Feng; Chen, Yulong
Abstract: Combined use of basalt fiber reinforced polymer (BFRP) and seawater sea-sand concrete (SSSC) in civil engineering could avoid the consumption of freshwater and river sand and solve the Chloride-induced corrosion problems. To promote the application and development of BFRP bars and SSSC, this paper presents an experimental study on BFRP bar reinforced SSSC columns under axial compression. Eight full-scale SSSC columns reinforced with BFRP bars were tested under axial compression. Failure modes, load–axial deformation curves, lateral deformation distributions, strains in BFRP bars and SSSC, initial axial stiffness, ultimate loads, and ductility of these column specimens were investigated. The effect of tie spacing, concrete strength, reinforcement ratio (i.e., longitudinal bar size) and slenderness ratio on the structural behaviour (e.g., ultimate load, initial stiffness, ductility, and strain distribution) of columns were analysed. Owing to the low modulus of BFRP, strength of BFRP is not fully utilized and the ultimate capacity of columns is mainly controlled by the compressive strength of concrete. Reducing tie spacing could increase the concrete compressive strength due to the confinement effect. Buckling of BFRP bars was postponed by increasing the confinement effect and bar size, resulting in an increase in the ultimate strain in bars. Although the slenderness ratio is low (=10.4–18.9), second-order effect exists in columns as evidenced by the failure modes of columns and the unequal axial strains of BFRP bars in the extreme tensile and compressive sides. Finally, design formulas are proposed to estimate the load-bearing capacity of BFRP bar reinforced SSSC columns and the prediction matches well with the experimental results. Highlights: Full-scale experiment on BFRP bar reinforced SSSC columns under axial compression. Effects of stirrup spacing, reinforcement ratio and slenderness on column behavior. Insufficient utilization of the strength of BFRP rebars to resist the axial load. Design method for column strength with the consideration of global stability.